2020
DOI: 10.5430/ijba.v11n4p21
|View full text |Cite
|
Sign up to set email alerts
|

Financial Impact of Irrigation and Nitrogen: Topdressing in Rural Enterprises of Sugarcane in Uruaçu, Brazil

Abstract: The success of a project depends on a good planning of activities focused on increasing yield and minimizing production costs. The objective of the present work was to assess the economic viability of irrigated sugarcane crops (plant crop and ratoon crop) under nitrogen topdressing, in northern state of Goiás (GO), Brazil. The data needed for the research were obtained in a sugarcane crop area in the Estrela do Lago Farm, which belongs to the Uruaçu industry, in the municipality of Uruaçu, GO. The CTC4 sugarca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…In respect to the costs of soil preparation, there were also no significant differences between SCMs (2.38) and SCSs (2.33). Therefore, the success of a rural property with sugarcane depends on good planning of activities focused on increasing yield and minimizing (Cunha & Pasqualetto, 2020;De Amorim et al, 2020). Finally, for planting costs, mills are more competitive than suppliers at 2.45 and 2.03, respectively ( The relative frequency graph SCS of the simulation regarding competitiveness indexes showed that the range between 2.27 and 2.35 contains the average indexes with a certainty level of 77.5% (Figure 1a), for suppliers with a 2.32 competitiveness index.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In respect to the costs of soil preparation, there were also no significant differences between SCMs (2.38) and SCSs (2.33). Therefore, the success of a rural property with sugarcane depends on good planning of activities focused on increasing yield and minimizing (Cunha & Pasqualetto, 2020;De Amorim et al, 2020). Finally, for planting costs, mills are more competitive than suppliers at 2.45 and 2.03, respectively ( The relative frequency graph SCS of the simulation regarding competitiveness indexes showed that the range between 2.27 and 2.35 contains the average indexes with a certainty level of 77.5% (Figure 1a), for suppliers with a 2.32 competitiveness index.…”
Section: Resultsmentioning
confidence: 99%
“…Brazilian agricultural commodities are relevant in the economic context, providing a positive economic and social performance for society (through job creation, for example). In this context, sugar (a by-product of sugarcane) has a competitive advantage in exports, being on the rise in the international trade market (Cunha & Pasqualetto, 2020;Sossa & Duarte, 2019). This competitiveness had a significant boost with the modernization of the sugar-energy sector since 1973.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation